DEVELOPMENT OF THE MAIN MACROECONOMIC INDICATORS AND THE FINAL CRISIS - Chagelishvili-Agladze, Lali; Aladashvili, Gela; Bagrationi, Nodar; Tavartkiladze, Amiran; Totladze, Lia; Agladze, Tamar (European Scientific Journal, ESJ, 2016)
On the background of global financial crisis, the successful solution of economic and social problems Georgia is facing is linked to the qualitative changes in the macro-economic efficiency, which is based on the construction of a market economy in Georgia. The reality of monetary policy developed by the National Bank and practical value is determined by how well it takes into account the results of country development of the and future objectives, the macroeconomic environment in the region, the ongoing processes in the world market. Established tendencies in Financial and foreign exchange markets, pricing changes and the factors affecting them, the hazards and their prevention, opportunities for adaptation to the changing environment in this policy. The paper analyzes and evaluates basic macroeconomic indicators of Georgia and gives positive and negative results of economic policy.